Prevalence of overweight/obesity in relation to dietary habits and lifestyle among 7–17 years old children and adolescents in Lithuania - Smetanina, Natalija (BMC Public Health, 2015)
BACKGROUND: Until recently increasing prevalence of overweight and obesity among pediatric population in Europe and worldwide contributes to major well-known risks for metabolic consequences in later life. The aim of this study was to determine the prevalence of overweight/obesity among children and adolescents in Lithuania and assess its association with energy balance related behaviors as well as familial demographic and socioeconomic factors. METHODS: Cross-sectional study included 3990 7–17 years old schoolchildren from 40 schools of Kaunas region, Lithuania. Study participants underwent anthropometric measurements. Body mass index (BMI) was evaluated according to International Obesity Task Force (IOTF) criteria for children and adolescents. Children and adolescents and their parents filled in the questionnaires on parental sociodemographic characteristics, dietary habits, TV watching time, and family socioeconomic status. RESULTS: The prevalence of underweight, overweight, and obesity among boys and girls was 6.9 and 11.7 % (P < 0.05), 12.6 and 12.6 % (P > 0.05), and 4.9 and 3.4 % (P < 0.05), respectively. Obesity was significantly more prevalent in the 7–9 years old group (6.7 and 4.8 % in boys and girls, respectively, P < 0.05). Lower meals frequency and breakfast skipping were directly associated with overweight/obesity (P < 0.05); however, physical inactivity was not associated with higher BMI. Children‘s overweight/obesity was directly associated with lower paternal education and unemployment (OR 1.30, P = 0.013 and OR 1.56, P = 0.003, respectively). CONCLUSIONS: The prevalence of overweight and obesity among 7–17 years old Lithuanian children and adolescents was more prevalent in younger age, still being one of the lowest across the European countries. Meals frequency, breakfast skipping, paternal education and unemployment as well as a family history of arterial hypertension were found to be associated with children’s and adolescents’ overweight/obesity.